The frequency and clinical presentation of Zika virus coinfections: a systematic review - Lobkowicz, Ludmila (BMJ Glob Health, 2020)
BACKGROUND: There is limited knowledge on the influence of concurrent coinfections on the clinical presentation of Zika virus (ZIKV) disease. METHODS: To better understand the types, frequencies and clinical manifestations of ZIKV coinfections, we did a systematic review of four databases (PubMed, Embase, Web of Science, LILACS) without restrictions for studies on ZIKV coinfections confirmed by nucleic acid (quantitative real-time-PCR) testing of ZIKV and coinfecting pathogens. The review aimed to identify cohort, cross-sectional, case series and case report studies that described frequencies and/or clinical signs and symptoms of ZIKV coinfections. Conference abstracts, reviews, commentaries and studies with imprecise pathogen diagnoses and/or no clinical evaluations were excluded. RESULTS: The search identified 34 articles from 10 countries, comprising 2 cohort, 10 cross-sectional, 8 case series and 14 case report studies. Coinfections were most frequently reported to have occurred with other arthropod-borne viruses (arboviruses); out of the 213 coinfections described, ZIKV infections co-occurred with chikungunya in 115 cases, with dengue in 68 cases and with both viruses in 19 cases. Other coinfecting agents included human immunodeficiency, Epstein-Barr, human herpes and Mayaro viruses, Leptospira spp, Toxoplasma gondii and Schistosoma mansoni. ZIKV-coinfected cases primarily presented with mild clinical features, typical of ZIKV monoinfection; however, 9% of cases in cohort and cross-sectional studies were reported to experience complications. CONCLUSION: Based on the evidence collated in this review, coinfections do not appear to strongly influence the clinical manifestations of uncomplicated ZIKV infections. Further research is needed to confirm whether risk of severe complications is altered when ZIKV infection co-occurs with other infections. PROSPERO REGISTRATION NUMBER: CRD42018111023.